EKRANISASI TEKS EKSPLANASI : EKRANISASI TEKS EKSPLANASI MENJADI GENRE FILM MELALUI MODEL PROJECT BASED LEARNING DAN PENGARUHNYA PADA KEMAMPUAN BERPIKIR KREATIF SISWA KELAS VIII SMP PRIBADI BANDUNG - Susanti, Yuniar; R. Panca Pertiwi Hidayati (Literasi: Jurnal Ilmiah Pendidikan Bahasa, Sastra Indonesia dan Daerah, 2024)
Students experience the degradation of digital technology. Students are becoming more proficient in operating devices and the applications they possess. Students of this generation need to be given stimuli to transform an explanatory text into another genre to make it more interesting and encourage creative thinking. This issue is observed among eighth-grade students at SMP Pribadi Bandung. The aim of this research is to describe ability to screenize (adapt into visual or multimedia form) explanatory texts on creative thinking through the project-based learning model among eighth-grade students at SMP Pribadi Bandung. The research method used is a quasi-experimental research method. Data collection techniques involve mixed methods (quantitative and qualitative). The results of the study show that eighth-grade students at SMP Pribadi Bandung were able to screenize explanatory texts into film genres based on the assessment rubric. The highest score obtained was 96, and the lowest score was 87, with an average score of 92. The students' ability to screenize explanatory texts into film genres is excellent. The students' ability to meet the structural and language rules in the films produced through the project-based learning model in eighth grade at SMP Pribadi Bandung achieved the highest post-test score of 100, with the lowest score being 80, and an average score of 89.9. The creative thinking ability of the students in the films they produced through the project-based learning model in eighth grade at SMP Pribadi Bandung is excellent. Out of 39 students, 36 students were categorized as capable of creative thinking, while three students were not yet able to think creatively. There is a very strong influence of the ability to screenize explanatory texts on creative thinking through the project-based learning model among eighth-grade students at SMP Pribadi Bandung, as confirmed by the hypothesis test.